Predictors of postoperative acute exacerbation of interstitial lung disease: a case–control study. Issue 1 (28th October 2020) - Hosoki, Keisuke; Mikami, Yu; Urushiyama, Hirokazu; Souma, Kunihiko; Kawamura, Gaku; Uchida, Kanji; Nagase, Takahide; Jo, Taisuke
Abstract : Introduction: Patients with interstitial lung disease (ILD) are known to develop an acute exacerbation (AE) after surgery. Previous studies have evaluated the predictors of postoperative AE. However, it remains unclear whether the results of those studies can be generalised to patients with different types of ILD and/or extrapolated to those who undergo non-pulmonary surgery. This study aimed to elucidate the predictors of the development of AE after surgery with general anaesthesia in patients with ILD. Methods: We conducted a nested matched case–control study of 700 patients from an initial cohort of 50 840 patients. We excluded those who underwent solid organ or bone marrow transplantation. The cases were patients with ILD who developed AE within 30 days postoperatively, whereas the controls did not develop AE. Each case (n=28) was matched with four controls (n=112) for sex, year of surgery and multiple operations within 30 days. Furthermore, a multivariable conditional logistic regression analysis was used to identify significant predictors, as indicated by a p value of <0.05. Results: After adjusting for potential confounders, the multivariable conditional logistic regression analysis identified honeycombing on CT (OR 3.09; 95% CI 1.07 to 8.92), a per cent predicted FVC <80% (OR 4.21; 95% CI 1.46 to 12.2) and an ARISCAT score ≥45 (OR 6.14; 95% CI 2.10 to 18.0) significantly associated with the development of postoperative AE. Conclusions: We found that the three factors were independent predictors for the development of postoperative AE in patients with ILD. These predictors are advantageous because they can be readily evaluated before surgery by surgeons and anaesthesiologists even without consulting experienced pulmonologists.